Timing matters: Endogenous cortisol mediates benefits from early-day psychotherapy. (December 2016) - Meuret, Alicia E.; Rosenfield, David; Bhaskara, Lavanya; Auchus, Richard; Liberzon, Israel; Ritz, Thomas; Abelson, James L.
Highlights: No "simple" determinant of enhanced extinction learning has been identified. Cortisol may act as facilitator of enhanced extinction learning. Early-day sessions yield better outcomes partly due to the enhancing effect of cortisol. Abstract: Objective: No simple way to augment fear extinction has been established. Cortisol has shown to enhance memory extinction and preliminary evidence suggest that extinction learning maybe more successful in the morning when cortisol is high. The aim was to determine whether exposure sessions conducted earlier in the day are associated with superior therapeutic gains in extinction-based psychotherapy. We also examined the role of cortisol levels as a mediator between time of day and therapeutic gains. Method: Participants were 24 individuals meeting DSM-IV criteria for panic disorder with agoraphobia. Participants received 3 weekly in-vivo exposure sessions, yielding 72 total sessions for analysis of time of day effects. Session start times were evenly distributed across the day. The outcome measures were reductions in panic symptom severity (avoidance behaviors, threat misappraisal, perceived control, and panic disorder symptom severity). Results: Sessions starting earlier in the day were associated with superior therapeutic gains by the next therapy session. Earlier sessions were also associated with higher pre-exposure cortisol levels, which in turn were related to greater clinical improvement by the next session. Cortisol thus was found to mediate the effect of time of day on subsequent outcome, providing a link between earlier exposure sessions and greater clinical improvement. Conclusion: The data suggest that early-day extinction-based therapy sessions yield better outcomes than later-day sessions, partly due to the enhancing effect of higher cortisol levels.